Efek Penghindaran Pajak, Tata Kelola, dan Sumber Pendanaan terhadap Nilai Perusahaan. - Rusnaidi; Tarmizi Gadeng; Wulan Dari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to examine the effect of tax avoidance, governance and funding sources on firm value. This research is a sample study, which includes 300 companies from 706 companies in the manufacturing sector during the 2017-2020 observation year with certain criteria. The analytical method used is fixed effect panel data regression model. The results of this study found that tax avoidance and funding sources have a negative effect on firm value. Corporate governance has a positive effect on firm value.